Case-based study on Biomass combustion power - Fei, Liu (My University, 2012)
China is regarded as world's biggest energy consumer. The continuously increased energy demand and use of fossil fuels has resulted in many environmental consequences, especially air pollutions and CO2 emission, which is key factor of global concern about climate change. China has always make efforts on promoting the development of renewable energy to take up the challenge of CO2 emission reduction. At the same time, China, as a large agricultural country as well, is abundant in biomass resources. As a renewable energy, biomass power generation has a rapid growth in past a few years in China. Many articles and reports study on the general situation of renewable energy or biomass utilization. Some conclusions are susceptible, since some arguments are conflicting with each other. A further investigation is necessary to know this industry at closer range. The aim of this project work is to investigate current situation of biomass direct combustion power generation in China. The study is case-based studies, which are often called bottom-up studies. The main results and conclusions come from comparison of projects visited during field study. Besides, general knowledge and analysis about biomass power industry used data from multiple sources including statistical reports, literature, regulations and policies. Most data is first-hand and untreated to make sure the reliability of result and conclusion. Through the analysis of the plant parameters, economy, system and related policies, currently the main obstacle for efficient application of biomass power generation is fuel source. To control fuel source is significant to run successful business. Policies provide the strong incentives to invest biomass power generation projects. The findings not only help to understand the current status of the industry, but also provide valuable experience to achieve a better future development
Keywords: Energi; Grundläggande vetenskaper; Hållbar utveckling; Maskinteknik; Energiteknik; Energy; Basic Sciences; Sustainable Development; Mechanical Engineering; Energy Engineering